Novel Compound Heterozygous PKLR Mutation Induced Pyruvate Kinase Deficiency With Persistent Pulmonary Hypertension in a Neonate: A Case Report - Lin, Sha; Hua, Xintian; Li, Jinrong; Li, Yifei (Frontiers in Cardiovascular Medicine, 2022)
Background: Pulmonary hypertension could be associated with pyruvate kinase deficiency (PKD). There are few reported cases of PPHN as the first clinical manifestation of PKD. Herein we report a rare case of PKD in which the patient exhibited persistent pulmonary hypertension in the neonate (PPHN), and genetic testing helped to rapidly identify an potential association. Case presentation: The patient was a newborn boy who suffered from severe dyspnea, extreme anemia, skin pallor, and hypoxemia. Repeated echocardiography indicated persistent severe pulmonary hypertension with a calculated pulmonary artery pressure of 75 mmHg, and right ventricular hypertrophy. The administration of nitric oxide significantly reduced the pulmonary artery pressure. Whole-exome sequencing revealed a compound heterozygous mutation consisting of c.707T>G and c.826_827insAGGAGCATGGGG. PolyPhen_2 and MutationTaster indicated that both the c.707T>G (probability 0.999) and c.826_827insAGGAGCATGGGG (probability 0.998) mutations were disease causing. PROVEAN protein batch analysis indicated that the associated p.L236R region was deleterious (score -4.71) and damaging (SIFT prediction 0.00), and this was also the case for p.G275_V276insEEHG (deleterious score -12.00, SIFT prediction 0.00). Substantial structural changes in the transport domain of the protein were predicted using SWISS-MODEL, and indicated that both mutations led to an unstable protein structure. Thus, a novel compound heterozygous mutation of PKLR-induced PKD with PPHN was diagnosed. Conclusion: The current study suggests that molecular genetic screening is useful for identifying PPHN, particularly in children with metabolic disorders. In patients exhibiting unexplained hyperbilirubinemia combined with severe pulmonary hypertension, PKD might be a potential possible alternative explanation. Genetic screening is helpful for identifying genetic causes of pulmonary hypertension, especially in patients with PPHN. This report expands the mutation spectrum of the PKLR gene, and contributes to the genotype-phenotype map of PKD.